Mosaic phenotypic evolution underlies the adaptive success of water-surface colonization in Gerromorpha - Zezhong Jin; Mu Qiao; Siying Fu; Zihe Li; Boxiong Guo; Hongjiao Li; Zhaoqi Leng; Matthew R. Pintar; Jakob Damgaard; Benjamin L. Makepeace; Silvia A. Mazzucconi; Gavril Marius Berchi; et al. (Proceedings of the National Academy of Sciences, 2026)
Understanding how the remarkable phenotypic diversity observed in organisms arises through shifts in macroevolutionary patterns and tempos is a fundamental challenge in evolutionary biology. Phenotypes often evolve in a mosaic pattern during adaptive transitions. For organisms that have invaded highly specialized habitats, such as the unique two-phase interface habitats (water surfaces), the macroevolutionary history of their phenotypic diversification remains only superficially understood. Semiaquatic bugs (Insecta: Heteroptera: Gerromorpha), which exhibit extensive habitat diversification and unparalleled phenotypic innovation, represent one of the most successful extant adaptive groups at this interface and provide an excellent system for study. By analyzing their adaptive transitions and phenotypic macroevolutionary history, we demonstrate that Gerromorpha experienced a single major adaptive transition from land to the water surface. Subsequently, semiaquatic bugs successfully colonized a wide range of distinct water-surface habitats. During this process, phenotypic space was explored under strong constraints and along pronounced mosaic trajectories; i.e., different body regions exhibited markedly distinct patterns of phenotypic space occupation and partitioning, as well as markedly different evolutionary rates. Furthermore, we showed that this mosaic pattern of phenotypic space occupation and rates of exploration had complex and critical effects on the invasion and colonization of water-surface habitats. Our study provides a typical case of macroevolutionary dynamics in species adapted to specialized air–water interface habitats, emphasizing the complex and significant roles of environmental context and functional demands in shaping patterns of phenotypic evolution.